2015
DOI: 10.1016/j.inat.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure alters cranial blood flow and cerebrospinal fluid dynamics at the craniovertebral junction

Abstract: Keywords:Cerebral blood flow Cerebrospinal fluid dynamics Spinal subarachnoid space Cerebral autoregulation Cervical spine Continuous positive airway pressure Sleep apnea Intrathoracic pressure Craniospinal compliance PtcCO 2 2D phase-contrast MRI Purpose: To investigate the impact of continuous positive airway pressure (CPAP) applied by a full-face fitted mask at 15 cmH 2 O on total cerebral blood flow (tCBF), jugular venous flow (tJVF) and cerebrospinal fluid (CSF) flow. Materials and methods: Axial 2D phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…In general, our CSF stroke volumes are somewhat higher, while our flow delays are somewhat lower, than those presented in the literature . This emphasizes that differences in spatial and time resolution, V enc , and even the approach to drawing the ROI, are important for the magnitude of such values.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In general, our CSF stroke volumes are somewhat higher, while our flow delays are somewhat lower, than those presented in the literature . This emphasizes that differences in spatial and time resolution, V enc , and even the approach to drawing the ROI, are important for the magnitude of such values.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study employed a higher encoding velocity than previous studies of aqueduct CSF net flow, which may explain some of the difference in the results. Some improvement in the reliability of this type of measurement may be achieved using PC‐MR sequences with multipoint velocity encoding . To provide a definitive answer as to whether the reversed CSF circulation is a component of the INPH pathophysiology, an alternative measurement technique is likely needed, for example, based on several repeated measurements or a long duration measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the internal carotid and vertebral arteries do not account for the entirety of arterial inflow to the head, and so the observed decrease in arterial inflow seen with HDT could also be due to diversion of arterial blood flow to other vessels. An alternative explanation could be due alterations in carbon dioxide levels due to anxiety and increased respiration while in HDT: Yiallourou et al previously had similar findings in changes in intracranial flow following alterations to carbon dioxide levels with the application of continuous positive airway pressure [31]. An additional limitation was that, due to time constraints, we did not repeat the scan protocol afterwards again in the supine position to assess for a return to baseline.…”
Section: Resultsmentioning
confidence: 96%
“…The statistically significant association of OSA with NPH is relatively novel [ 18 •• ] but the physiopathological vascular and metabolic mechanisms have been amply supported in the literature [ 66 71 , 74 – 80 ]. For instance, pulmonary hypertension is a well-known effect of OSA [ 82 ] and positive end-expiratory pressure (PEEP) [ 83 85 ] can increase central venous pressure, decreasing outflow and elevating intracranial CSF pressure. Frydrychowski et al [ 86 ] showed that acute increases in jugular vein pressure induce elevation of intracranial CSF pressure.…”
Section: Introductionmentioning
confidence: 99%